ANALISIS STRATEGI PEMASARAN PRODUK DANA DAN JASA BANK PADA BANK KALBAR KANTOR CABANG UTAMA PONTIANAK - maulana Filani Rizal; Naiyun Untung Utama; Angga Hendarsa (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2021)
ABSTRACT Every company that is built has goals and objectives to be achieved, thus all functions and activities carried out by the company must always be managed and directed by using all available resources optimally for the creation of these goals and objectives. The purpose of this study was to determine the marketing strategy of fund products and bank services at Bank Kalbar. This research was conducted to find out how big the respondent's response regarding the marketing strategy, especially the 7P marketing strategy namely Place, Price, Promotion, Product, People, Process, Physical Evidence. The research method used is a survey method with the object of public research being the customer and target of Bank Kalbar. Data collection techniques used in the form of observation, interviews and questionnaires distributed to all West Kalimantan Bank customers as many as 30 respondents who then the data are grouped according to existing criteria and the results of each question answer are added, from the sum results the percentage is determined and a conclusion is drawn. Based on the results of the study it can be concluded that the marketing strategy undertaken by Bank Kalbar on the marketing of fund products and bank services such as place, price, promotion, product, people, process, physical evidence seen from the whole is good. Based on the calculation process, an average total score of 26.06 was obtained with an overall average score of 3.72. So based on these calculations it can be said that the marketing strategy of place, price, promotion, product, people, process, physical evidence carried out by Bank Kalbar in the good category, amounted to 3.72 in the range from 3.40 to 4.19. Keywords: Marketing Policy; Extrinsic (place, price, promotion, product, people, process, physical evidence)